Overcoming adaptive resistance to anti-VEGF therapy by targeting CD5L - LaFargue, Christopher J.; Amero, Paola; Noh, Kyunghee; Mangala, Lingegowda S.; Wen, Yunfei; Bayraktar, Emine; Umamaheswaran, Sujanitha; Stur, Elaine; Dasari, Santosh K.; Ivan, Cristina; Pradeep, Sunila; Yoo, Wonbeak; et al. (Nature communications, 2023)
Antiangiogenic treatment targeting the vascular endothelial growth factor (VEGF) pathway is a powerful tool to combat tumor growth and progression; however, drug resistance frequently emerges. We identify CD5L (CD5 antigen-like precursor) as an important gene upregulated in response to antiangiogenic therapy leading to the emergence of adaptive resistance. By using both an RNA-aptamer and a monoclonal antibody targeting CD5L, we are able to abate the pro-angiogenic effects of CD5L overexpression in both in vitro and in vivo settings. In addition, we find that increased expression of vascular CD5L in cancer patients is associated with bevacizumab resistance and worse overall survival. These findings implicate CD5L as an important factor in adaptive resistance to antiangiogenic therapy and suggest that modalities to target CD5L have potentially important clinical utility. The efficacy of antiangiogenic therapy in the clinic is often limited by the emergence of resistance. Here, the authors show that in ovarian cancer anti-VEGF inhibitors induce the overexpression of CD5L in endothelial cells through hypoxia-driven PPARy activation and that blocking CD5L can overcome resistance.